Cancer-associated fibroblasts promote pro-tumor functions of neutrophils in pancreatic cancer via IL-8: potential suppression by pirfenidone - Tomohiko Yagi; Shunsuke Kagawa; Shohei Nogi; Atsuki Taniguchi; Masashi Yoshimoto; Kanto Suemori; Yasuo Nagai; Shuto Fujita; Shinji Kuroda; Satoru Kikuchi; Yoshihiko Kakiuchi; Fuminori Teraishi; et al. (Cancer Immunology, Immunotherapy)
Abstract Background The mechanisms by which neutrophils acquire pro-tumor properties remain poorly understood. In pancreatic cancer, cancer-associated fibroblasts (CAFs) may interact with neutrophils, directing them to promote tumor progression. Methods To validate the association between CAFs and neutrophils, the localization of neutrophils was examined in clinically resected pancreatic cancer specimens. CAFs were produced by culturing in cancer-conditioned media, and the effects of these CAFs on neutrophils were examined. In vitro migration and invasion assays assess the effect of CAF-activated neutrophils on cancer cells. The factors secreted by the activated neutrophils were also explored. Finally, pirfenidone (PFD) was tested to determine whether it could suppress the pro-tumor functions of activated neutrophils. Results In pancreatic cancer specimens, neutrophils tended to co-localize with IL-6-positive CAFs. Neutrophils co-cultured with CAFs increased migratory capacity and prolonged life span. CAF-affected neutrophils enhance the migratory and invasive activities of pancreatic cancer cells. IL-8 is the most upregulated cytokine secreted by the neutrophils. PFD suppresses IL-8 secretion from CAF-stimulated neutrophils and mitigates the malignant traits of pancreatic cancer cells. Conclusion CAFs activate neutrophils and enhance the malignant phenotype of pancreatic cancer. The interactions between cancer cells, CAFs, and neutrophils can be disrupted by PFD, highlighting a potential therapeutic approach.